Decomposition of wild jack (Artocarpus hirsutus Lamk.) leaf litter under subcanopy and open conditions - Isaac, Sheeba Rebecca; Nair, M. Achuthan (Journal of Tropical Agriculture, 2006)
A comparative study on in situ and ex situ decomposition dynamics of wild jack (Artocarpus hirsutus Lamk.) leaf litter was conducted in a homegarden of Southern Kerala, India. Results of the litter bag study indicate that under the canopy 95% of the litter mass disappeared in about 17 fortnights, whereas in the open it took approximately 19 fortnights. Weight loss followed a negative exponential model and the half-lives were 9.45 and 10.31 fortnights respectively for in situ and ex situ decomposition. Earthworm and microbial counts were also substantially greater in the subcanopy than in the open, implying a favourable effect of the subcanopy conditions. Nutrient dynamics exhibited temporary phases of immobilization for both N and P, while K release was continuous.